Teacher Perception on EFL Students' Engagement in Project-Based Learning - Nur Hasanah Safei; Salmah Salmah (AL LUGHAWIYAAT, 2022)
This qualitative study is aims to find out the teacher perception of EFL student's engagement in ptoject-based learning (BPL). Project-based learning may enhance their skills of English (i.e., speaking, reading and writing). The participantsof this study the syntax lecturer from class B of five semester of English education department. The qualitative data were analyzed by interview from the syntax lecturer and students' artifact/documents. The results revealed that students showed significant progress in their learning process. Theu also confirmed that project based learning in student involvement to help students to understand the practice and challenges of the industries. In addition, based on the result of this study, it seems that project-based learning has a positive impact on the learning process.